Evaluation value of ultrasound on gastrointestinal function in patients with acute heart failure - Ruyi Hao; Ye Zheng; Qing Zhao; Jie Chen; Ruiqi Fan; Peng Chen; Na Yin; Huai Qin (Frontiers in Cardiovascular Medicine)
ObjectiveTo study the changes in gastrointestinal wall thickness, blood flow, motility, and symptoms in patients with acute heart failure, and to assess gastrointestinal function by ultrasound.MethodsIn this study, patients diagnosed with acute heart failure were selected as the study group, and healthy individuals were selected as the control group. Both groups collected general data and completed the Chinese version of the gastrointestinal symptom rating scale. Ultrasonography was used to measure several abdominal vascular and gastrointestinal-related indicators. Statistical analysis used grouped comparison and correlation analysis.ResultsThe study group scored higher than the control group in total score, lower abdominal symptom score, constipation score, and difficult defecation score (Z = −2.828, −2.022, −2.015, −2.015, all P < 0.05). The hepatic vein diameter, superior mesenteric vein inner diameter and wall thickness of the ascending colon in the study group were significantly higher than those in the control group (t = 9.543, P < 0.001; t = 2.277, P = 0.025; Z = −2.062, P = 0.039). Antral contraction amplitude, antral contraction frequency, motility index, jejunal peristalsis frequency, and ascending colon peristalsis frequency were significantly lower in the study group compared to the control group (Z = −2.571, −4.196, −3.681, −5.451, −4.061, all P < 0.001). The wall thickness of the antrum, jejunum, and ascending colon were positively correlated with the diameter of the hepatic vein (r = 0.394, P = 0.011; r = 0.352, P = 0.024; r = 0.450, P = 0.003). Motility index and ascending colon peristalsis frequency were positively correlated with the peak velocity of superior mesenteric vein (r = 0.456, P = 0.029; r = 0.507, P = 0.007). The wall thickness of the jejunum was positively correlated with the peak velocity of superior mesenteric artery (r = 0.330, P = 0.035). Peak velocity of superior mesenteric artery, antral contraction frequency, and jejunal peristalsis frequency were negatively correlated with the reflux score (r = −0.409, P = 0.038; r = −0.423, P = 0.032; r = −0.409, P = 0.038). The wall thickness of the ascending colon was positively correlated with the reflux score (r = 0.414, P = 0.035).ConclusionThis study found that patients with acute heart failure exhibited thickening of the gastrointestinal wall and generally reduced gastrointestinal motility, with predominantly lower abdominal symptoms. These findings indicate that ultrasound can effectively monitor the gastrointestinal structure and function of patients with acute heart failure, which is expected to provide help for clinical diagnosis and treatment.